Paleo‐Antarctic rainforest into the modern Old World tropics: The rich past and threatened future of the "southern wet forest survivors"1. Issue 12 (1st December 2014) - Kooyman, Robert M.; Wilf, Peter; Barreda, Viviana D.; Carpenter, Raymond J.; Jordan, Gregory J.; Sniderman, J. M. Kale; Allen, Andrew; Brodribb, Timothy J.; Crayn, Darren; Feild, Taylor S.; Laffan, Shawn W.; Lusk, Christopher H.; et al.
Abstract : Premise of study: Have Gondwanan rainforest floral associations survived? Where do they occur today? Have they survived continuously in particular locations? How significant is their living floristic signal? We revisit these classic questions in light of significant recent increases in relevant paleobotanical data. Methods: We traced the extinction and persistence of lineages and associations through the past across four now separated regions—Australia, New Zealand, Patagonia, and Antarctica—using fossil occurrence data from 63 well‐dated Gondwanan rainforest sites and 396 constituent taxa. Fossil sites were allocated to four age groups: Cretaceous, Paleocene–Eocene, Neogene plus Oligocene, and Pleistocene. We compared the modern and ancient distributions of lineages represented in the fossil record to see if dissimilarity increased with time. We quantified similarity–dissimilarity of composition and taxonomic structure among fossil assemblages, and between fossil and modern assemblages. Key results: Strong similarities between ancient Patagonia and Australia confirmed shared Gondwanan rainforest history, but more of the lineages persisted in Australia. Samples of ancient Australia grouped with the extant floras of Australia, New Guinea, New Caledonia, Fiji, and Mt. Kinabalu. Decreasing similarity through time among the regional floras of Antarctica, Patagonia, New Zealand, and southern Australia reflects multiple extinction events. Conclusions: Gondwanan rainforest lineages contribute significantly to modern rainforest community assembly and often co‐occur in widely separated assemblages far from their early fossil records. Understanding how and where lineages from ancient Gondwanan assemblages co‐occur today has implications for the conservation of global rainforest vegetation, including in the Old World tropics.